PENGARUH DISIPLIN BELAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN ADMINISTRASI PERKANTORAN - Ramadani, Suci; Br Tarigan, Rika Tresia; Sihombing, Ronaida; Siregar, Putri Fadhila; Umar, Andi Taufiq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of learning discipline (X1) and learning motivation (X2) on student learning outcomes measured through Grade Point Average (GPA) in the Department of Office Administration Education. This research uses a quantitative approach with survey methods. The sample consisted of 50 respondents selected from second-semester and fourth-semester students. Data were collected through a questionnaire instrument and analyzed using Pearson correlation analysis and multiple linear regression. The results showed that partially, learning discipline (t = -0.722, p = 0.474 > 0.05) and learning motivation (t = 1.524, p = 0.135 > 0.05) did not significantly affect student learning outcomes. Simultaneously, both variables also did not significantly affect learning outcomes (F = 1.386, p = 0.261 > 0.05). The coefficient of determination (R²) was only 0.058, meaning that learning discipline and learning motivation only explained 5.80% of the variation in student GPA. This finding suggests that student learning outcomes are primarily determined by other factors outside of discipline and motivation alone, such as teaching quality, learning environment, and students' cognitive abilities. These findings contribute to the discussion on factors affecting academic performance in higher education.